Effectiveness of micro-jets at different level of expansion - Chaudhary, Zakir Ilahi; Vilas B., Shinde; Khan, Sher Afghan (www.iosrjournals.org, 2015)
An experimental investigation was conducted to study the effectiveness of micro jets to control base pressure in suddenly expanded axi-symmetric duct. Since active control is used to control the base pressure and hence the base drag the air is drawn from the main settling chamber to the control chamber to control the base pressure, hence it doesn’t require additional source of energy for the control mechanism. The flow parameters considered in this investigation are the Mach number (1.2, 1.3, 1.5, 1.9, 2.2, 2.6, and 3.0) at the exit of the nozzle, and the ratio of the pressure in the main settling chamber to the ambient pressure (NPR). The geometrical parameters considered are the area ratio between the sudden expansion duct cross-section and the nozzle exit area, and the duct length-to-diameter ratio (10 to 1). The area ratio considered was 3.24. The experiments were done for NPRs in the range from 3 to 11 in a step of 2 for all the Mach numbers. The wall pressure distribution in the suddenly expanded duct was also measured and it is seen from the static wall that the control does not affect the wall static pressure adversely. When the micro jets were activated they were found to influence the base region, taking the base pressure to considerably higher values compared to that for without control, for most of the cases. However, there are certain combinations of parameters for which the active control results in decrease of base pressure.